Population Pharmacokinetics and Antimalarial Pharmacodynamics of Piperaquine in Patients With Plasmodium vivax Malaria in Thailand. (27th August 2014) - Tarning, J; Thana, P; Phyo, AP; Lwin, KM; Hanpithakpong, W; Ashley, EA; Day, NPJ; Nosten, F; White, NJ
Abstract : Dihydroartemisinin‐piperaquine is an effective drug in the treatment of Plasmodium falciparum and P. vivax malaria. The objective of this study was to evaluate the population pharmacokinetics and pharmacodynamics of piperaquine in patients with P. vivax malaria in Thailand after a standard regimen of dihydroartemisinin‐piperaquine to determine whether residual piperaquine prevents or delays the emergence of P. vivax relapse. Sparse blood samples were collected from 116 patients. Piperaquine pharmacokinetics were described well by a three‐compartment distribution model. Relapsing P. vivax malaria was accommodated by a constant baseline hazard (8.94 relapses/year) with the addition of a surge function in a fixed 3‐week interval and a protective piperaquine effect. The results suggest that a large proportion of the first relapses were suppressed completely by residual piperaquine concentrations and that recurrences resulted mainly from emergence of the second or third relapse or from reinfection. This suggests a significant reduction in P. vivax morbidity when using dihydroartemisinin‐piperaquine compared with other antimalarial drugs with shorter terminal postprophylactic effects. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e132; doi:10.1038/psp.2014.29 ; published online 27 August 2014